Rozwiązane

rozwiąż zadanie i zrób sprawdzenie 4 (x - 2) = 2x+6. 5x-1=4(x+3). 2m-4=6m+8​



Odpowiedź :

Amona

4 (x - 2) = 2x+6                                      Sprawdzenie:

4x - 8 = 2x + 6                                      4 (x - 2) = 2x+6

4x - 2x = 6 + 8                                      4(7-2) = 2*7 + 6

2x = 14         /:2                                     4*5 = 14 + 6

x = 7                                                      20 = 20

5x-1=4(x+3)                                            Sprawdzenie:

5x - 1 = 4x + 12                                        5x-1=4(x+3)  

5x - 4x = 12 + 1                                        5*13 - 1 = 4(13+3)

x = 13                                                      65 - 1 = 4*16

                                                              64 = 64

2m-4=6m+8​                                            Sprawdzenie:

2m - 6m = 8 +4                                         2m-4=6m+8​  

-4m = 12           /:(-4)                                  2*(-3) -4 = 6*(-3) + 8

m = -3                                                       -6 - 4 = -18 + 8

                                                                -10 = -10